Improving and enhancing scenario planning: futures thinking - Crawford, Megan M.; Wright, George (Edward Elgar Publishing, 2025)
"This book presents a contemporary view of the approaches and theories that inform global scenario planning and foresight science, providing practical recommendations for improving scenario development processes. Its insights bridge the gap between last century's foundations and this century's innovations. Megan M. Crawford and George Wright bring together a global team of expert authors to illustrate the development of scenario storylines and the role of a facilitator in team-based activities and processes. They detail practical scenario applications, provide guidance for practice improvement, and analyse the use of scenario thinking in strategic choice. Together, the authors show the path of scenario development, from foundation to validation, and explore new and broader views of futures thinking, scenario methodologies, innovative developments, and practical applications that reflect the evolution of the field. With guidance for practitioners and support for academics across the fields of futures and foresight science, Improving and Enhancing Scenario Planning is a valuable resource. Students of business, management, innovation and technology will also find this book beneficial"--